Global calculation of neoclassical impurity transport including the variation of electrostatic potential. (June 2020) - Fujita, Keiji; Satake, S.; Kanno, R.; Nunami, M.; Nakata, M.; García-Regaña, J. M.; Velasco, J. L.; Calvo, I.
Abstract : Recently, the validity range of the approximations commonly used in neoclassical calculation has been reconsidered. One of the primary motivations behind this trend is observation of an impurity hole in LHD (Large Helical Device), i.e. the formation of an extremely hollow density profile of an impurity ion species, such as carbon C^6+, in the plasma core region where a negative radial electric field ( E_r ) is expected to exist. Recent studies have shown that the variation of electrostatic potential on the flux surface, [STIX]x1D6F7_1, has significant impact on neoclassical impurity transport. Nevertheless, the effect of [STIX]x1D6F7_1 has been studied with radially local codes and the necessity of global calculation has been suggested. Thus, we have extended a global neoclassical code, FORTEC-3D, to simulate impurity transport in an impurity hole plasma including [STIX]x1D6F7_1 globally. Independently of the [STIX]x1D6F7_1 effect, an electron root of the ambipolar condition for the impurity hole plasma has been found by global simulation. Hence, we have considered two different cases, each with a positive (global) and a negative (local) solution of the ambipolar condition, respectively. Our result provides another support that [STIX]x1D6F7_1 has non-negligible impact on impurity transport. However, for the ion-root case, the radial C^6+ flux is driven further inwardly by [STIX]x1D6F7_1 . For the electron-root case, on the other hand, the radial particle C^6+ flux is outwardly enhanced by [STIX]x1D6F7_1 . These results indicate that how [STIX]x1D6F7_1 affects the radial particle transport crucially depends on the profile of the ambipolar- E_r, which is found to be susceptible to [STIX]x1D6F7_1 itself and the global effects.